Investigation of the in vivo and in silico wound healing property of Retama raetam (Forssk) Webb & Berthel. leaves extract - Hafsia Bouzenna; Hmed Ben Nasr; Najla Hfaeidh; Ahlem Missaoui; Angelo Maria Giuffrè; Karim Hosni; Samira Jebahi; Naceur Mejri (Frontiers in Pharmacology, 2025)
In this study, the wound healing properties of the leaf aqueous extract of Retama raetam (Forssk) Webb & Berthel was investigated in vivo and in silico. The HPLC-DAD profiling of bioactive compounds allowed the identification of five phenolics including quercetin, kaempferol, naringenin, myricetin and caffeic acid. The aqueous extract has been found to significantly inhibit microbial growth in the wounded tissue contributing thereby to its cleansing. The topical application of the aqueous extract accelerated wound closure and enhanced the re-epithelialization and restoration of damaged wound skin. The wound healing activity of the R. raetam which was supported by histopathological observations exceeded that of the standard wound healing cream biafine. Concomitantly, the wound-repairing action was associated with a reduced oxidative stress as revealed by the decrease of lipid peroxidation versus the activation of antioxidant enzymes SOD, CAT and GPx. In silico study showed that naringenin and to a less extent myricetin have the highest bending capacity to the active site of pro-inflammatory cytokines TNF-α and IL-1β receptors. These results indicate that R. raetam could be considered as a consolidated source of putative bioactive phenolics with excellent antioxidant, antimicrobial, anti-inflammatory and wound healing properties, offering thereby experimental and theoretical supports for its application in the treatment of burn skin wounds.